Quantitative analysis of the evolution of ASR products and crack networks in the context of the concrete mesostructure. (December 2022) - Shakoorioskooie, Mahdieh; Griffa, Michele; Leemann, Andreas; Zboray, Robert; Lura, Pietro
Abstract: Methodological challenges have long been an obstacle for the understanding of damage in concrete due to the alkali-silica reaction (ASR). Time-lapse X-ray tomography could be key to advancements but has not been extensively exploited, mainly due to similar electron densities of the different material phases, which leads to poor contrast in the tomograms. To address this limitation, we propose the implementation of two complementary contrast agents, BaSO4 and CsNO3 . After optimizing the contents of both agents synergistically for mortars, we realize for the first time a quantitative characterization of the spatial-temporal distributions of both ASR products and cracks, while differentiating their presence in aggregates and in cement paste. This new methodology allowed showing that similar amounts of ASR products were found inside the aggregates and inside the cement paste. The transport of products from inner aggregate regions into the cement paste along propagating cracks was followed in 4D.